Livestock and aquaculture farming in Bangladesh: Current and future challenges and opportunities - Kieron, M.; Eeswaran, R.; Pouyan Nejadhashemi, A.; Sebastian Hernandez- Suarez, J. (Taylor & Francis, 2023)
We conducted a comprehensive review of livestock farming in Bangladesh to unveil current challenges and potential opportunities in this agricul- ture sector. Six challenges were selected as the major constraints to livestock farming in Bangladesh: climate change and natural hazards, poor veterinary care, breeding and management resources, marketing and international trade, and the SARS-CoV-2 pandemic. Solutions to these challenges (such as hazardous weather shelters, intensified surveillance of biosecurity for farms and markets, and non- government, government, and private organizations working together to educate and assist farmers) must target specific regions where the solutions would have the greatest effect.
Keywords: Livestock; Bangladesh; Aquaculture; Ruminant; Fishery; Cattle